Public policies on information and collective intelligence: The challenges and possibilities for the democratization of information - Franco, Angela Halen Claro [UNESP]; Carvalho, Angela Maria Grossi [UNESP]; Amorim da Costa Santos, Plácida Leopoldina Ventura [UNESP] (Universidade Federal da Paraíba, 2019)
The social information paradigm presents multiples challenges for the interactive knowledge time of Information Science, especially whit regard to the use of collective intelligence in digital environments. In this context, the collective intelligence manifests itself as a proposal that aims at harnessing individual skills for the development of a Knowledge space. The provision of technological infrastructure and digital competences for the insertion of individuals in this space requires the establishment of efficient public policies for the information area. Therefore, through the exploratory and descriptive analysis, it is intended to bring information policies closer to collective intelligence. It was observed that ideals of democratization of information was common to both fields, and that defining consistent public information polices is viable alternative for the realization of the Knowledge space, and consequently for the valorization of collective intelligence.
Políticas públicas de informação e inteligência coletiva: os desafios e as possibilidades para a democratização da informação
Keywords: Collective intelligence; Communication technologies; Information; Information public policies; Public policies